Electrical transport in lead-free (Na0.5Bi0.5)1–xSrxTiO3 ceramics (x = 0, 0.01 and 0.02). (2nd September 2017) - Dutkiewicz, E.M.; Suchanicz, J.; Konieczny, K.; Czaja, P.; Kluczewska, K.; Czternastek, H.; Antonova, M.; Sternberg, A.
ABSTRACT: Lead-free (Na0.5 Bi0.5 )1 x Sr x TiO3 ( x = 0, 0.01 and 0.02) ceramics were manufactured through a solid-state mixed oxide method and their ac (σac ) and dc (σdc ) electric conductivity were studied. It is shown that the low-frequency (100 Hz–1 MHz) ac conductivity obeys a power law σac ∼ ω s characteristic for disordered materials. Both the dc and ac conductivities have thermally activated character and possess linear parts with different activation energies. The calculated activation energies are attributed to different mechanism of conductivity. Frequency dependence of σdc and exponent s is reasonably interpreted by a correlated barrier hopping model. The NBT-ST system is expected to be a new promising candidate for lead-free electronic materials.